Effect of Gas Type and Its Pressure on Nanobubble Generation - Bunkin, Nikolai F.; Shkirin, Alexey V.; Penkov, Nikita V.; Goltayev, Mikhail V.; Ignatiev, Pavel S.; Gudkov, Sergey V.; Izmailov, Andrey Yu. (Frontiers in Chemistry, 2021)
The dependence of the bulk density of ion-stabilized gas nanobubbles (bubstons) on the type of gas and the pressure, created by this gas in deionized water and saline solution, has been investigated. The range of external pressures from the saturated water vapor (17 Torr) to 5 atm was studied. It turned out that the velocity of growth of the volume number density of bubstons is controlled by the magnitude of the molecular polarizability of the dissolved gases. The highest densities of bubstons were obtained for gases, the molecules of which have the dipole moment. At fixed external pressure and polarizability of gas molecules, the addition of external ions leads to a sharp increase in the content of bubstons.